Steady-State 3D Trapping and Manipulation of Microbubbles Using Thermocapillary - Muñoz-Pérez, F. M.; Ortega-Mendoza, J. G.; Padilla-Vivanco, A.; Toxqui-Quitl, C.; Sarabia-Alonso, J. A.; Ramos-García, R. (Frontiers in Physics, 2020)
An experimental and theoretical study on the 3D trapping and manipulation of microbubbles by means low power laser-induced temperature gradients induced in ethanol by bulk light absorption (λ = 1550 nm) is presented. Two optical fibers were used: One for bubble generation (OFG) and the other for both trapping and manipulation (OFT). Light from a Q-switched pulsed laser (λ=532 nm & pulse width τp=5 ns) propagates in fiber OFG and gets absorbed at silver nanoparticles (AgNPs), previously photodeposed, at the distal end of a fiber optic core, generating the microbubbles. In the fiber OFT, light of low power CW laser was used to trap and manipulate the bubbles by thermocapillary induced by light bulk absorption in ethanol. The microbubble generated on OFG migrates towards the fiber OFT. The equilibrium between the buoyancy force FB, drag force FD and the Marangoni force (also known as thermocapillary force) FM gives rise to a 3D stably trapping and manipulation of the microbubble for the best time to our best knowledge.